APPLICATION OF THE TEXTUAL INFORMATION ANALYSIS METHOD FOR THE PROBLEM OF CLASSIFICATION OF SCIENTIFIC ARTICLE - N. O. Ukhanov; K. G. Yachshenkov; K. S. Dymko; A. V. Khnykin (Современная наука и инновации)
The problem of classification of scientific articles is considered.